0
$\begingroup$

Can anyone help me to find the mean value of the displacement operator $$D(\alpha) = \exp( \alpha a^\dagger -\alpha^* a)$$ for a Coherent State $\left|\beta\right> = D\left(\beta\right)\left|0\right>$?

$\endgroup$
  • 1
    $\begingroup$ Hi! Welcome to QCSE! This question seems unmotivated right now. Please provide some details of what you are asking and what you know. $\endgroup$ – Mark S Oct 1 at 0:30
1
$\begingroup$

So you want to calculate $\left<\beta |D\left(\alpha\right)|\beta\right>$ where $\left|\beta\right>$ is a coherent state and $D\left(\alpha\right)$ is the displacement operator.

The easiest way of doing this is to take $\left<\beta |D\left(\alpha\right)|\beta\right> = \left<0|D^\dagger\left(\beta\right) D\left(\alpha\right)D\left(\beta\right)|0\right>$ and write this in terms of the exponential of creation and annihilation operators $D(\alpha) = \exp( \alpha a^\dagger -\alpha^* a)$, which I'll denote as $D(\alpha) = \exp(Y)$.

At this point, note that $D^\dagger(\beta) = \exp( \beta^* a -\beta a^\dagger) = D\left(-\beta\right) = \exp(-X)$ and from here, we can use the Baker–Campbell–Hausdorff formula. In this case, $$\left[X,Y\right] = \left[\beta a^\dagger -\beta^* a,\alpha a^\dagger -\alpha^* a\right] = \beta\alpha^*\left[a, a^\dagger\right] - \beta^*\alpha\left[a, a^\dagger\right] = \beta\alpha^* - \beta^*\alpha$$ as $\left[a, a^\dagger\right] = 1$.

As $\beta\alpha^* - \beta^*\alpha$ is just a constant, this commutes with both $\beta a^\dagger -\beta^* a$ and $\alpha a^\dagger -\alpha^* a$ and so, all the higher order terms in BCH are $0$.

This gives that $e^{-X}e^Y = e^{-X+Y-\frac{1}{2}\left[X, Y\right]}$ and further that $$e^{-X}e^Ye^X = e^{-X+Y-\frac{1}{2}\left[X, Y\right] + X + \frac{1}{2}\left[-X+Y-\frac{1}{2}\left[X, Y\right],X\right]} = e^{Y - \left[X, Y\right]}.$$

While this still looks complicated, $\left[X, Y\right] = \beta\alpha^* - \beta^*\alpha$ is still a constant, so we can rewrite this as $$\left<0|e^{-X}e^Ye^X|0\right> = \left<0|e^{-\left[X, Y\right]}e^Y|0\right> = e^{-\left[X, Y\right]}\left<0|e^Y|0\right>.$$

At this point, we can write $e^Y\left|0\right> = D\left(\alpha\right)\left|0\right> = e^{-\frac{1}{2}\left|\alpha\right|^2}e^{\alpha a^\dagger}\left|0\right>$ (which can also be shown using BCH) to get $$\left<\beta |D\left(\alpha\right)|\beta\right> = e^{-\beta\alpha^* + \beta^*\alpha}\left<0|e^{-\frac{1}{2}\left|\alpha\right|^2}e^{\alpha a^\dagger}|0\right> = e^{-\beta\alpha^* + \beta^*\alpha - \frac{1}{2}\left|\alpha\right|^2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.